Dysregulated Phosphorylation of p53, Autophagy and Stemness Attributes the Mutant p53 Harboring Colon Cancer Cells Impaired Sensitivity to Oxaliplatin - Therachiyil, Lubna; Haroon, Javeria; Sahir, Fairooz; Siveen, Kodappully S.; Uddin, Shahab; Kulinski, Michal; Buddenkotte, Joerg; Steinhoff, Martin; Krishnankutty, Roopesh (Frontiers in Oncology, 2020)
Colorectal cancer (CRC) forms one of the highest ranked cancer types in the world with its increasing incidence and mortality rates despite the advancement in cancer therapeutics. About 50% of human colorectal cancers are reported to have defective p53 expression resultant of TP53 gene mutation often contributing to drug resistance. The current study was aimed to investigate the response of wild-type TP53 harboring HCT 116 and mutant TP53 harboring HT 29 colon cancer cells to chemotherapeutic drug oxaliplatin (OX) and to elucidate the underlying molecular mechanisms of sensitivity/resistance in correlation to their p53 status. OX inhibited growth of wild-type p53-harboring colon cancer cells via p53/p21-Bax mediated apoptosis. Our study revealed that dysregulated phosphorylation of p53, autophagy as well as cancer stemness attributes the mutant p53-harboring colon cancer cells impaired sensitivity to oxaliplatin.